Expression and regulation of CYP17A1 and 3β-hydroxysteroid dehydrogenase in cells of the nervous system: Potential effects of vitamin D on brain steroidogenesis. (February 2018) - Emanuelsson, Ida; Almokhtar, Mokhtar; Wikvall, Kjell; Grönbladh, Alfhild; Nylander, Erik; Svensson, Anne-Lie; Fex Svenningsen, Åsa; Norlin, Maria
Abstract: Steroids are reported to have diverse functions in the nervous system. Enzymatic production of steroid hormones has been reported in different cell types, including astrocytes and neurons. However, the information on some of the steroidogenic enzymes involved is insufficient in many respects. Contradictory results have been reported concerning the relative importance of different cell types in the nervous system for expression of CYP17A1 and 3β-hydroxysteroid dehydrogenase (3β-HSD). 3β-HSD is important in all basic steroidogenic pathways and CYP17A1 is required to form sex hormones. In the current investigation we studied the expression of these enzymes in cultured primary rat astrocytes, in neuron-enriched cells from rat cerebral cortex and in human neuroblastoma SH-SY5Y cells, a cell line often used as an in vitro model of neuronal function and differentiation. As part of this study we also examined potential effects on CYP17A1 and 3β-HSD by vitamin D, a compound previously shown to have regulatory effects in steroid hormone-producing cells outside the brain. The results of our study indicate that astrocytes are a major site for expression of 3β-HSD whereas expression of CYP17A1 is found in both astrocytes and neurons. The current data suggest that neurons, contrary to some previous reports, are not involved in 3β-HSD reactions. Previous studies have shown that vitamin D can influence gene expression and hormone production by steroidogenic enzymes in some cells. We found that vitamin D suppressed CYP17A1-mediated activity by 20% in SH-SY5Ycells and astrocytes. Suppression of CYP17A1 mRNA levels was considerably stronger, about 50% in SH-SY5Y cells and 75% in astrocytes. In astrocytes 3β-HSD was also suppressed by vitamin D, about 20% at the enzyme activity level and 60% at the mRNA level. These data suggest that vitamin D-mediated regulation of CYP17A1 and 3β-HSD, particularly on the transcriptional level, may play a role in the nervous system. Highlights: Expression of steroidogenic enzymes were studied in different CNS cell cultures. CYP17A1 activity was observed in both neuronal cell cultures and astrocytes. 3β-hydroxysteroid dehydrogenase (3β-HSD) activity was found only in astrocytes. Vitamin D suppressed mRNA levels and activities of 3β-HSD and CYP17A1. The biological actions of vitamin D may involve effects on brain steroidogenesis.